Religion og politik i antik jødedom og tidlig kristendom - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 1983)
Initially, definitions of religion and politics are discussed. Then the issue as regards the Mediterranean areas is surveyed in general. The ideas of Eddy and Fuchs are adopted. Ancient Jewish history and literature from 175 B.C. to A.D. 135 are analysed under this point of view, and it is found that in all Jewish trends the religious and the political spheres overlap to a variable high degree. In early Christianity we find a main stream of non-political “quetism” dominated almost totally by the religious sphere. Another trend is more political and more influenced by Judaism. Jesus is found to belong to this latter trend. This means that in the movement of Jesus, religion and politics were closely united. As a consequence, a major transformation of early Christianity is supposed to have taken place early in its history. This transformation is finally assumed to be closely connected with the dissociation between the early Christians and the Jews. After the separation from Judaism, Christianity became an individualistic and spiritualistic religion with little room for the political sphere. This situation changed again in the 4th century with the revolution of Constantine when the Christian religion again was connected with the decisive powers in society.